If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-4)=12x-4-9x
We simplify the equation to the form, which is simple to understand
3(x-4)=12x-4-9x
Reorder the terms in parentheses
+(+3x-12)=12x-4-9x
Remove unnecessary parentheses
+3x-12=+12x-4-9x
We move all terms containing x to the left and all other terms to the right.
+3x-12x+9x=-4+12
We simplify left and right side of the equation.
0x=+8
0=8
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 2x^3-15x^2+24x+12=0 | | (50x-8y)+(32x+37y)= | | 24+x=-18 | | -3x^2-12x+1=0 | | 28=w(2w-1) | | (x-2)(x+4)=14 | | x^2+x-36= | | 12c+5=c+31 | | 35x+-14=36x+-6 | | -18=x+20 | | 36x-14=36x-6 | | -22=11(2c-8) | | |-14|= | | (22-18)x(3+8)= | | x-24=6 | | 2(2)+3(4a)-4(3+3a)+3=0 | | 3y-24-6y+37= | | 4d^2-4d-80=0 | | x-8.8=-6.8 | | 2=2m+2+6m | | (q*q*q)-6(q*q)-21600=0 | | 12/3x5-16 | | 10-x/4x | | 6(2x+2)+15= | | -2/-1 | | 0=x^4-6x^3-x^2+20x | | 2.6-5.1=6.6 | | 3x/4-1/3(3x-6)=5/2(6-x/2) | | 6(2x^2-9x-18)=0 | | 8x/3-2x-6 | | 11x^3-x+9=x^3+45x^2+x | | 683+2x=53 |